A HUMAN IRONY IN SHIRLEY JACKSON'S THE LOTTERY - ANGGRIAWAN, DEVRY (Jurnal Ilmiah Mahasiswa FIB, 2013)
This study is aimed to analyze the short story The Lottery to reveal the human irony. To analyze the data, the writer applied Peircean semiotics. The results of data analysis indicate that there is a human irony reflected by the sign in the short story that is The Lottery itself. The discovery of human irony in this short story is done through three levels of understanding the theory of Peircean semiotics. For better study, the writer suggests that English Literature students dig The Lottery because there are many aspects that can be analyzed more deeply for example, using the theory of psychology to examine each character and theory of Cultural Studies to examine the terms and traditions contained in this short story.   Keywords: short story “The Lottery”, human irony, Peircean semiotics.